Factors Influencing Water Consumption in the Kingdom of Bahrain and Environmental Consequences of Bottled Water Consumption - Freije, A. M.; Hammad, L. H.; Al-Mannai, M.; Perna, S. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The drinking of bottled water has remarkably increased at a global scale even in the regions possessing other adequate water sources. This study elaborates on the factors influencing the consumption of tap, filtered, and bottled water in the Kingdom of Bahrain and on the environmental consequences of bottled water consumption.Methods. A cross-sectional study was performed on 483 participants in the Kingdom of Bahrain between April and May 2019. A questionnaire-based survey was conducted to assess the preferred water type, to estimate the amount of bottled water consumption per year/capita, and other water consumption-related information.Results. The study revealed that filtered (35.90%) and bottled (34.50%) waters were predominantly consumed in the Kingdom, while the consumption of tap water was negligible (8.90%). The total consumption of bottled water was 0.51 liters/day, which is equivalent to 184.69 liters/year. Thus, 295.50 liters/capita/year of bottled water were consumed based on the approximate 1.6 million population in 2019. This consumption rate is extremely high in comparison to other countries.Conclusions. The study recommended improving population satisfaction of tap water, conducting tap water marketing campaigns, investments in recycling infrastructures, and introducing educational plans to properly dispose of water bottles.